Factors Associated with Performance of Farmer Field School as Extension Approach to Cocoa Production in Osun State, Nigeria - Adisa , B. O; K. A, Adeloye (Asian Journal of Agriculture and Rural Development, 2012)
The study focused on factors associated with performance of Farmer Field School (FFS) as extension approach to cocoa production in Osun State, Nigeria. Data were gathered through structured interview schedule from 248 cocoa farmers participating in FFS. Data collected were analyzed using descriptive statistical tools such as frequency counts, percentage, mean and standard deviation while inferential statistics such as correlation and chi square were used to test the hypothesis set. Results of the study show that the mean age of cocoa farmers participating in FFS in the study area was 53.3 years with standard deviation of 9.0; majority (79.4%) of them were males, they spent an average of 10.9 years in formal school, the mean of years of experience in cocoa production was 7.5 with standard deviation of 4.8 and they had progressive increase in cocoa output from 2007 to 2009. Furthermore, there was high compliance with the organizational structure and operational strategies recommended by Food and Agriculture Organization (FAO). There were positive and significant relationship between improvement in cocoa management practices and respondents’ age (r = 0.322; P ≤ 0.05); years of formal education(r = 0.153; P ≤ 0.05); cocoa land size(r = 0.501; P ≤ 0.01); years of experience in cocoa production (r = 0.503; P ≤ 0.01). The study also identified five crucial factors associated with performance of FFS as extension approach, which were social factor (λ = 1.0706); economic factor (λ = 1.2549); facilitators-related factor (λ = 1.6744); FFS operational strategies factor (λ = 0.9973); and community-related factor (λ = 0.4767). The factors indentified explained 83.50 percent of the variation in the performance of FFS as extension approach to cocoa production in Osun State.